Surface protection paper adhesion glue and preparation method thereof
By using modified starch and modified glucose in the protective paper adhesive glue, the problem of reduced adhesion and insufficient durability of the glue in high humidity environment is solved, and stronger adhesion strength, moisture resistance and durability are achieved.
Patent Information
- Application Number
- CN202411407245.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-02-25
AI Technical Summary
The adhesion force of the existing protective paper adhesive is reduced in high humidity environments, and the durability is poor, making it difficult to maintain excellent adhesion under different environmental conditions.
Modified starch and modified glucose are added to the glue, and the cross-linking degree and bonding performance between starch molecules are enhanced through physical modification and chemical cross-linking modification.
It significantly improves the adhesive strength, moisture resistance and durability of the glue, so that it can maintain good bonding performance during long-term use and under different environmental conditions.
Smart Images

Figure BDA0005076979740000021 
Figure BDA0005076979740000091 
Figure BDA0005076979740000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glue, and in particular relates to a face paper adhesion glue and a preparation method thereof. Background Art
[0002] Gypsum board, also known as gypsum wallboard or gypsum panel, is a common building material, mainly used for the decoration and construction of indoor walls and ceilings. It is made of one or more layers of thick paperboard (face paper) wrapped with a dry gypsum core (the main component is calcium sulfate hemihydrate CaSO4·1 / 2H2O). Gypsum board has the advantages of easy installation, good fire resistance, high flatness, good flexibility, and the ability to improve acoustic effects. In construction, gypsum board is widely used in wall partitions, ceiling systems, decorative purposes, etc.
[0003] In order to increase the bonding performance between the face paper and the gypsum core, glue is usually placed between the two. According to the composition of the glue, it can be divided into natural glue, synthetic resin, etc., and some auxiliary additives such as plasticizers, waterproofing agents, preservatives, etc. are also added to the glue to improve the overall performance of the gypsum board. Although the adhesive glue used between the face paper and the gypsum core in the paper-faced gypsum board can effectively ensure a good combination of the paper surface and the gypsum core in most cases, it also has some potential disadvantages:
[0004] (1) In high humidity environments, the glue may be affected, resulting in a decrease in the bond between the paper cover and the gypsum core, especially when exposed to a humid environment for a long time;
[0005] (2) Over time, the glue may age, especially under conditions of frequent temperature changes, causing separation between the paper backing and the gypsum core.
[0006] In response to the above-mentioned problems of glue in terms of environmental humidity and durability, the methods currently available are:
[0007] (1) Adding enhancers, such as polymer emulsions, epoxy resins and other synthetic resins, to the glue to improve durability and moisture resistance, but the above-mentioned enhancers may produce harmful substances, which is not conducive to environmental protection;
[0008] (2) Add moisture-proofing agents, such as silane coupling agents and silicones, to the glue to reduce the impact of moisture on the glue. However, the moisture-proofing agent is likely to be incompatible with the original material, affecting the overall performance.
[0009] (3) Pre-treatment of the paper surface or gypsum core, such as coating with a moisture-proof coating, can further enhance the performance of the glue, but this surface treatment method increases the complexity of production, production time and cost.
[0010] Therefore, there is an urgent need for a safe, environmentally friendly, low-cost, and durable face paper adhesive glue. Summary of the invention
[0011] The purpose of the present invention is to provide a face paper adhesive glue and a preparation method thereof, so as to solve the problem that the moisture resistance and durability of the above-mentioned glue are poor. The present invention adds modified starch and modified glucose to the glue, so that the glue not only performs well in the initial bonding, but also maintains its excellent bonding performance in long-term use and under different environmental conditions.
[0012] To achieve the above object, the first aspect of the present invention provides a face paper adhesive glue, which comprises the following raw materials in parts by weight:
[0013]
[0014] The preparation process of modified starch is:
[0015] S11: mixing amylose and amylopectin in a mass ratio of (3-5):1 to obtain mixed starch;
[0016] S12: Mixing the mixed starch and fiber powder in a mass ratio of 100:(10-15) to obtain a mixed powder;
[0017] S13: preparing a 3-5% aqueous solution of an alkali metal salt having a mass percentage of 0.1-0.2% of the mixed powder, and then spraying the solution into the mixed powder, allowing the mixture to stand for equilibrium, drying, crushing, and sieving the mixture, and treating the mixture with hot air flow at 120-140° C. for 3-5 hours to obtain a physically modified starch;
[0018] S14: adding epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate in a mass ratio of 1:1:(0.3-0.5) to a 75-90% ethanol aqueous solution, mixing well, to obtain a mixed solution;
[0019] S15: adding the mixed solution to the physically modified starch, mixing evenly, and obtaining a mixed material;
[0020] S16: heating the mixture to 40-50° C. and adjusting the pH value to 11-11.3 to obtain a reaction mass;
[0021] S17: adding ferric sulfate and 30% hydrogen peroxide to the reaction material, stirring to completely react, and then drying and gelatinizing to obtain modified starch;
[0022] The preparation method of modified glucose is:
[0023] S21: Glucose, methanol, dimethyl sulfoxide and Amberlyst-15 resin are added into a reactor, which is sealed and placed at 100-120° C. for reaction for 8-12 hours, and then filtered to obtain an intermediate product;
[0024] S22: adding polyacrylic acid, malonic acid and succinic anhydride into water in a mass ratio of 1:(2-4):1 and mixing to obtain a cross-linking solution;
[0025] S23: adding the cross-linking solution to the intermediate product, reacting at 100-120° C. for 1-2 hours to obtain modified glucose.
[0026] Preferably, the starch is at least one of waxy corn starch, tapioca starch, potato starch, corn starch, glutinous rice starch and wheat starch.
[0027] Preferably, the alkali metal salt is one of sodium hydroxide or potassium hydroxide.
[0028] Preferably, the fiber powder comprises citrus fiber, inulin and apple fiber in a mass ratio of 1:1:(3-5).
[0029] Preferably, in step S14, the mass ratio between the total mass of epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate and the ethanol aqueous solution is 1:(120-150).
[0030] Preferably, the mass ratio of epichlorohydrin to physically modified starch in the mixed solution in step S15 is 1 to 1.5:100.
[0031] Preferably, in step S17, the mass ratio of ferric sulfate to physically modified starch is (0.2-0.4):100, and the mass ratio of hydrogen peroxide to physically modified starch is (3-5):100.
[0032] Preferably, in step S21, the mass volume ratio of glucose to methanol is 0.8-1.0 g:1-1.5 mL, the mass ratio of glucose to Amberlyst-15 resin is 1:(0.2-0.3); and the volume ratio of methanol to dimethyl sulfoxide is 1:(3-5).
[0033] Preferably, in step S23, the mass ratio of the total mass of polyacrylic acid, malonic acid and succinic anhydride to glucose is 1:(3-4).
[0034] Starch-based face paper adhesive glue has been widely used in many industries because of its natural resource, low cost, and non-toxicity. Although starch-based glue has many advantages, it also has various shortcomings in practical application, such as poor water resistance, limited bonding strength, and poor durability. In view of the above problems, the present invention proposes to modify starch. First, the starch is subjected to a physical process of steps S11-S13 to improve its application performance by changing the structure and properties of starch particles. In this process, amylose and amylopectin are mixed in a certain proportion and combined with fiber powder, and then treated with alkali metal salts and hot air flow. After treatment, the starch particles are easier to disperse, and their solubility and fluidity in water are improved, thereby enhancing the bonding performance of the glue.
[0035] After the starch granules are physically modified, the bonding performance of the glue can be improved, but further research has found that its moisture resistance and durability are not greatly improved. In order to further improve the comprehensive performance of the starch-based glue, the physically modified starch is further chemically cross-linked. The present invention introduces specific chemical reagents to change the chemical structure of starch molecules, specifically chemical reagents such as epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate, which can increase the cross-linking degree between starch molecules, so that it can still maintain a high bonding strength in a humid environment. In addition, chemical modification can also make the starch glue have better storage stability and service life.
[0036] Therefore, the present invention performs physical modification and chemical modification on starch successively, which can significantly improve the bonding performance, durability and moisture resistance of the adhesive glue for face paper. The physical modification mainly enhances the basic bonding force and ease of use of the glue, while the chemical modification further improves the comprehensive performance of the glue, making it more stable and reliable under different conditions.
[0037] In order to further improve the bonding performance of the glue, the present invention adds small molecule sugar glucose, which can play a thickening role in the glue system, increase the viscosity of the glue, and thus improve its bonding force. The present invention continues to study and find that although the addition of pure glucose can improve the bonding performance of the glue, it does not significantly improve the service life and environmental resistance of the glue. The present invention continues to study and find that modifying glucose can improve the moisture resistance and durability of the glue. Analysis of the reasons: Due to the change in its chemical structure, the modified glucose can better interact with starch or other components during the curing process, promote the glue to form a continuous film on the surface of the substrate, thereby enhancing the bonding effect. The modified glucose contains some special functional groups, which can form additional cross-linking points with starch molecules, increase the stability of the internal structure of the glue, and thus improve its durability for long-term use. The chemical modification of the modified glucose may introduce some hydrophobic groups or enhance the internal cross-linking density of the glue, so that the glue will not easily lose its viscosity even in a humid environment. Due to the presence of modified glucose, the glue can still maintain its structural integrity after absorbing water, and is not easy to swell, thereby maintaining good bonding performance.
[0038] The second aspect of the present invention provides a method for preparing a face paper adhesive glue, comprising the following steps:
[0039] S1: Add starch and modified starch to water heated to 40-80° C., and after fully dissolving, obtain a starch solution;
[0040] S2: Continue to add glucose and modified glucose to the starch solution and mix well;
[0041] S3: adding sodium hydroxide to the uniformly mixed solution in step S2, and continuing stirring to obtain a face paper adhesive glue, wherein the pH value of the face paper adhesive glue is 8-13.
[0042] Therefore, the present invention adopts the above-mentioned face paper adhesive glue and preparation method thereof, which has the following beneficial effects:
[0043] 1. The present invention uses modified starch and modified glucose. The chemical modification in the modification process increases the interaction force between molecules, so that the glue can provide stronger adhesion when adhering to the face paper, and the adhesion strength of the glue can be significantly improved.
[0044] 2. The modified starch and modified glucose in the present invention are specially treated to resist moisture erosion and maintain good adhesion even in a humid environment, which makes the face paper less susceptible to humidity changes during use and extends its service life.
[0045] 3. The introduction of the modified components of the present invention improves the overall durability of the glue, so that it can still maintain a high adhesive performance after long-term use, which means that the facial paper product can maintain a good appearance and function for a long time.
[0046] 4. The modified components of the present invention help to improve the fluidity and coating performance of the glue, so that the glue can be more evenly distributed on the face paper during the application process, reducing defects in the coating process, such as bubbles or uneven distribution, thereby improving the quality of the finished product.
[0047] 5. Compared with traditional chemical synthetic glue, the present invention uses natural starch and glucose as the basic materials, and improves the performance through physical and chemical modifications, reducing the use of harmful chemicals, which is not only beneficial to environmental protection, but also meets the current market demand for green packaging materials. DETAILED DESCRIPTION
[0048] The present invention will be further described below. It should be noted that this embodiment is based on the technical solution and provides a detailed implementation method and a specific operation process, but the present invention is not limited to this embodiment.
[0049] Example 1
[0050] This embodiment provides a face paper adhesive, which includes the following raw materials in parts by weight:
[0051] 20 parts of starch, the starch is corn starch;
[0052] 9 parts of modified starch;
[0053] 4 parts of glucose;
[0054] 1.5 parts of modified glucose;
[0055] 3 parts of sodium hydroxide;
[0056] 65 parts of deionized water.
[0057] The preparation process of modified starch is:
[0058] S11: mixing amylose and amylopectin in a mass ratio of 4:1 to obtain mixed starch;
[0059] Amylose was purchased from Shanghai Yuanye Biotechnology Co., Ltd., model number S11003, and amylopectin was purchased from Shanghai Yuanye Biotechnology Co., Ltd., model number S11002;
[0060] S12: Mixing the mixed starch and the fiber powder in a mass ratio of 100:12 to obtain a mixed powder; the fiber powder includes citrus fiber, inulin and apple fiber in a mass ratio of 1:1:4; the citrus fiber is purchased from Shaanxi Guben Biotechnology Co., Ltd., the inulin is purchased from Nanjing Xinte Biotechnology Co., Ltd., and the apple fiber is purchased from Shanxi Aite Biotechnology Co., Ltd.;
[0061] S13: preparing a 4% aqueous solution of an alkali metal salt having a mass percentage of 0.15% of the mixed powder, and then spraying the solution into the mixed powder, allowing the mixture to stand for equilibrium, drying, crushing, and sieving, and treating the mixture with hot air at 135° C. for 4 hours to obtain a physically modified starch; the alkali metal salt is sodium hydroxide;
[0062] S14: adding epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate to 80% ethanol aqueous solution in a mass ratio of 1:1:0.4, and mixing them evenly to obtain a mixed solution; the mass ratio between the total mass of epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate and the ethanol aqueous solution is 1:130;
[0063] S15: adding the mixed solution to the physically modified starch, mixing evenly, to obtain a mixed material; the mass ratio of epichlorohydrin to the physically modified starch in the mixed solution is 1.2:100;
[0064] S16: heating the mixture to 45° C. and adjusting the pH value to 11.2 to obtain a reaction mass;
[0065] S17: adding ferric sulfate and 30% hydrogen peroxide to the reaction material, stirring to completely react, and then drying and gelatinizing to obtain modified starch;
[0066] The mass ratio of ferric sulfate to physically modified starch is 0.3:100, and the mass ratio of hydrogen peroxide to physically modified starch is 4:100.
[0067] The preparation method of modified glucose is:
[0068] S21: Glucose (CAS No.: 492-62-6), methanol, dimethyl sulfoxide, and Amberlyst-15 resin were added into a reactor, sealed, and reacted at 110° C. for 10 h, and then filtered to obtain an intermediate product; Amberlyst-15 resin was purchased from Merrill, brand M79644;
[0069] The mass volume ratio of glucose to methanol is 0.8 g:1.2 mL, the mass ratio of glucose to Amberlyst-15 resin is 1:0.2; the volume ratio of methanol to dimethyl sulfoxide is 1:4;
[0070] S22: adding polyacrylic acid (CAS No.: 9003-01-4), malonic acid and succinic anhydride (CAS No.: 108-30-5) into water in a mass ratio of 1:3:1 and mixing to obtain a cross-linking solution; the mass ratio of the total mass of polyacrylic acid, malonic acid and succinic anhydride to water is 1:50;
[0071] S23: adding the cross-linking solution to the intermediate product, reacting at 110° C. for 1.5 h, filtering and drying to obtain modified glucose; the mass ratio of the total mass of polyacrylic acid, malonic acid and succinic anhydride to glucose is 1:3.5.
[0072] A method for preparing a face paper adhesive glue comprises the following steps:
[0073] S1: Add starch and modified starch into water heated to 50° C. and fully dissolve to obtain a starch solution;
[0074] S2: Continue to add glucose and modified glucose to the starch solution and mix well;
[0075] S3: adding sodium hydroxide to the uniformly mixed solution in step S2, and continuing stirring to obtain a face paper adhesive glue, wherein the pH value of the face paper adhesive glue is 10.
[0076] Example 2
[0077] The difference between this embodiment and embodiment 1 is that the formula of the adhesive for bonding the face paper is different.
[0078] A face paper adhesive glue, comprising the following raw materials in parts by weight:
[0079]
[0080] Comparative Example 1
[0081] The difference between this comparative example and Example 1 is that during the preparation of the modified starch, the mass ratio of amylose to amylopectin is 10:1.
[0082] Comparative Example 2
[0083] The difference between this comparative example and Example 1 is that during the preparation of the modified starch, the fiber powder includes citrus fiber, inulin and apple fiber in a mass ratio of 1:1:10.
[0084] Comparative Example 3
[0085] The difference between this comparative example and Example 1 is that during the preparation of the modified starch, epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate are in a mass ratio of 1:1:1.
[0086] Comparative Example 4
[0087] The difference between this comparative example and Example 1 is that the physically modified starch is directly added as the modified starch into the glue preparation process.
[0088] Comparative Example 5
[0089] The difference between this comparative example and Example 1 is that starch that has only been chemically modified is added as modified starch into the glue preparation process.
[0090] The preparation process of chemically modified starch in this comparative example is:
[0091] The preparation process of modified starch is:
[0092] S11: mixing amylose and amylopectin in a mass ratio of 4:1 to obtain mixed starch;
[0093] Amylose was purchased from Shanghai Yuanye Biotechnology Co., Ltd., model number S11003, and amylopectin was purchased from Shanghai Yuanye Biotechnology Co., Ltd., model number S11002;
[0094] S12: adding epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate to 80% ethanol aqueous solution in a mass ratio of 1:1:0.4, and mixing them evenly to obtain a mixed solution; the mass ratio between the total mass of epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate and the ethanol aqueous solution is 1:130;
[0095] S13: adding the mixed solution to the mixed starch, mixing evenly, to obtain a mixed material; the mass ratio of epichlorohydrin in the mixed solution to the mixed starch is 1.2:100;
[0096] S14: heating the mixture to 45° C. and adjusting the pH value to 11.2 to obtain a reaction mass;
[0097] S15: adding ferric sulfate and 30% hydrogen peroxide to the reaction material, stirring to completely react, and then drying and gelatinizing to obtain chemically modified starch;
[0098] The mass ratio of ferric sulfate to physically modified starch is 0.3:100, and the mass ratio of hydrogen peroxide to physically modified starch is 4:100.
[0099] Comparative Example 6
[0100] The difference between this comparative example and Example 1 is that the mixed starch is directly added as modified starch into the glue preparation process.
[0101] Comparative Example 7
[0102] The difference between this comparative example and Example 1 is that during the preparation of modified glucose, the mass ratio of polyacrylic acid, malonic acid and succinic anhydride is 3:3:1.
[0103] Comparative Example 8
[0104] The difference between this comparative example and Example 1 is that the modified glucose is not modified by methanol but directly cross-linked.
[0105] The preparation method of modified glucose in this comparative example is:
[0106] S21: adding polyacrylic acid, malonic acid and succinic anhydride to water in a mass ratio of 1:3:1 and mixing to obtain a cross-linking solution; the mass ratio of the total mass of polyacrylic acid, malonic acid and succinic anhydride to water is 1:50;
[0107] S22: Glucose is added to the cross-linking solution, and reacted at 110° C. for 1.5 hours to obtain modified glucose; the mass ratio of the total mass of polyacrylic acid, malonic acid and succinic anhydride to glucose is 1:3.5.
[0108] Comparative Example 9
[0109] The difference between this comparative example and Example 1 is that the modified glucose is not cross-linked but only etherified.
[0110] The preparation process of modified glucose in this comparative example is:
[0111] S21: Glucose, methanol, dimethyl sulfoxide, and Amberlyst-15 resin were added into the reactor, sealed, and reacted at 110° C. for 10 h, and filtered to obtain an intermediate product;
[0112] The mass volume ratio of glucose to methanol is 0.8 g:1.2 mL, the mass ratio of glucose to Amberlyst-15 resin is 1:0.2; the volume ratio of methanol to dimethyl sulfoxide is 1:4;
[0113] S21: Drying the intermediate product to obtain etherified glucose.
[0114] Comparative Example 10
[0115] The difference between this comparative example and Example 1 is that glucose is directly added to the glue preparation process instead of modified glucose.
[0116] Performance Testing
[0117] The glue prepared in the examples and comparative examples was applied in the preparation process of gypsum boards.
[0118] The preparation process of gypsum board is:
[0119] (1) Choose ordinary directly purchased gypsum core (surface density 6.5kg / m 2 , thickness 9.5mm) and directly purchased face paper as raw materials;
[0120] (2) The surface of the face paper is evenly coated with the glue prepared in the examples and comparative examples, with a coating amount of 15 g / m 2 , then place the lower surface of the gypsum core on the facing paper coated with glue, and then place another facing paper coated with glue on the upper surface of the gypsum core;
[0121] (3) Use rolling equipment to tightly adhere the facing paper to the surface of the gypsum core and naturally cure it for 24 hours to obtain a gypsum board.
[0122] According to the relevant methods in GB / T 9775-2008 "Paper-faced gypsum board", the dry and wet peel strength of the gypsum board was tested. The wet strength sample processing method is: the gypsum board is placed in hot water (65℃) for 3 hours, dried after the soaking, and tested within half an hour. The gypsum board is placed at 70 degrees Celsius for 12 hours, taken out and cooled to room temperature, then placed at -20 degrees Celsius for 12 hours, taken out and warmed to room temperature, and so on for ten times to test its peel strength. The test results are shown in Table 1.
[0123] Wet peel strength retention rate = (dry peel strength - wet peel strength) / dry peel strength x 100%.
[0124] The peel strength retention rate after 10 heating and freezing cycles = (dry peel strength - peel strength after 10 heating and freezing cycles) / dry peel strength × 100%.
[0125] Table 1 Performance test results
[0126]
[0127] It can be seen from the above performance test results that the glue of Examples 1-2 has good bonding performance, moisture resistance and durability, especially the comprehensive performance of Example 1 is the most outstanding. This is mainly because modified starch and modified glucose are added to the glue. Through the synergistic effect of multiple mechanisms, not only the initial bonding performance of the glue is enhanced, but also it can ensure that it still maintains excellent bonding effect for a long time and under humid conditions, thereby improving the overall performance.
[0128] However, the comparative examples are significantly worse than the embodiments in terms of corresponding performance tests because they do not adopt the necessary technical solutions. Comparative examples 1-3 respectively change the mass ratios of amylose and amylopectin, three fiber powders, epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate in the preparation process of modified starch. It can be seen from the results that the adhesive properties of the glue prepared by them decrease after use, and the water resistance and durability also decrease. This shows that the ratio setting in the modified starch will affect the comprehensive properties of the glue and have an impact on the improvement of its comprehensive properties. In comparative example 4, only the first step of physical modification is involved in the preparation process of modified starch. It can be seen from the results that the adhesive properties, water resistance and durability of the glue decrease significantly. In comparative example 5, only the second step of cross-linking chemical modification is carried out in the preparation process of modified starch. It can be seen from the results that the adhesive properties, water resistance and durability of the glue also decrease significantly. This shows that the modified starch in the present invention is physically modified and cross-linked chemically modified in sequence, which has an important influence on the improvement of the comprehensive properties of the glue. In Comparative Example 6, mixed starch (i.e. starch that has not been physically and chemically modified) is directly added to the glue preparation process. From the results, it can be seen that the bonding performance, water resistance and durability of the glue prepared by it are further reduced, indicating the necessity of two-step modification of starch in the present invention. The modification of starch plays a very important role in improving the comprehensive performance of glue. Comparative Example 7 changes the mass ratio of polyacrylic acid, malonic acid and succinic anhydride in the preparation process of modified glucose. From the results, it can be seen that the comprehensive performance of the glue prepared by it is reduced, indicating that the ratio of the three plays an important role in improving the comprehensive performance of glue. The modified glucose in Comparative Example 8 is only cross-linked modified by polyacrylic acid, malonic acid and succinic anhydride, and no etherification modification is performed. From the results, it can be seen that the bonding performance, water resistance and durability of the glue prepared by it are significantly reduced. The modified glucose in Comparative Example 9 is only etherified modified by methanol, and the second step of cross-linking modification is not performed. From the results, it can be seen that the comprehensive performance of the glue is significantly reduced. Comparative Examples 8-9 illustrate the necessity of first etherification modification of glucose and then cross-linking modification, and the two-step modification of modified glucose has an important influence on improving the comprehensive performance of glue. In Comparative Example 10, unmodified glucose is directly added to the glue preparation process. From the results, it can be seen that the comprehensive performance of the glue prepared by it is further reduced, indicating that the use of modified glucose in the present invention has a very important influence on improving the bonding performance, water resistance and durability of the glue. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0129] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A face paper adhesive glue, characterized in that: The following raw materials are included in parts by weight: The preparation process of modified starch is: S11: mixing amylose and amylopectin in a mass ratio of (3-5):1 to obtain mixed starch; S12: Mixing the mixed starch and fiber powder in a mass ratio of 100:(10-15) to obtain a mixed powder; S13: preparing a 3-5% aqueous solution of an alkali metal salt having a mass percentage of 0.1-0.2% of the mixed powder, and then spraying the solution into the mixed powder, allowing the mixture to stand for equilibrium, drying, crushing, and sieving the mixture, and treating the mixture with hot air flow at 120-140° C. for 3-5 hours to obtain a physically modified starch; S14: adding epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate in a mass ratio of 1:1:(0.3-0.5) to a 75-90% ethanol aqueous solution, mixing well, to obtain a mixed solution; S15: adding the mixed solution to the physically modified starch, mixing evenly, and obtaining a mixed material; S16: heating the mixture to 40-50° C. and adjusting the pH value to 11-11.3 to obtain a reaction mass; S17: adding ferric sulfate and 30% hydrogen peroxide to the reaction material, stirring to completely react, and then drying and gelatinizing to obtain modified starch; The preparation method of modified glucose is: S21: Glucose, methanol, dimethyl sulfoxide and Amberlyst-15 resin are added into a reactor, which is sealed and placed at 100-120° C. for reaction for 8-12 hours, and then filtered to obtain an intermediate product; S22: adding polyacrylic acid, malonic acid and succinic anhydride into water in a mass ratio of 1:(2-4):1 and mixing to obtain a cross-linking solution; S23: adding the cross-linking solution to the intermediate product, reacting at 100-120° C. for 1-2 hours, and obtaining modified glucose.
2. The adhesive for bonding face paper according to claim 1, characterized in that: The starch is at least one of waxy corn starch, tapioca starch, potato starch, corn starch, glutinous rice starch and wheat starch.
3. The adhesive for bonding face paper according to claim 1, characterized in that: The alkali metal salt is one of sodium hydroxide or potassium hydroxide.
4. The adhesive for bonding face paper according to claim 1, characterized in that: The fiber powder includes citrus fiber, inulin and apple fiber in a mass ratio of 1:1:(3-5).
5. The adhesive for bonding face paper according to claim 1, characterized in that: The mass ratio between the total mass of epichlorohydrin, sodium trimetaphosphate and sodium chloroacetate and the ethanol aqueous solution in step S14 is 1: (120-150).
6. The adhesive for bonding face paper according to claim 1, characterized in that: The mass ratio of epichlorohydrin to physically modified starch in the mixed solution in step S15 is 1 to 1.5:
100.
7. The adhesive for bonding face paper according to claim 1, characterized in that: In step S17, the mass ratio of ferric sulfate to physically modified starch is (0.2-0.4):100, and the mass ratio of hydrogen peroxide to physically modified starch is (3-5):
100.
8. The adhesive for bonding face paper according to claim 1, characterized in that: In step S21, the mass volume ratio of glucose to methanol is 0.8-1.0 g:1-1.5 mL, the mass ratio of glucose to Amberlyst-15 resin is 1:(0.2-0.3); the volume ratio of methanol to dimethyl sulfoxide is 1:(3-5).
9. The adhesive for bonding face paper according to claim 1, characterized in that: In step S23, the mass ratio of the total mass of polyacrylic acid, malonic acid and succinic anhydride to glucose is 1:(3-4).
10. The method for preparing the adhesive for face paper according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1: Add starch and modified starch to water heated to 40-80° C., and after fully dissolving, obtain a starch solution; S2: Continue to add glucose and modified glucose to the starch solution and mix well; S3: adding sodium hydroxide to the uniformly mixed solution in step S2, and continuing stirring to obtain a face paper adhesive glue, wherein the pH value of the face paper adhesive glue is 8-13.